On boundary-value problems for second order perturbed differential inclusions - Dhage, B. C.; Graef, J. R. (Applicable analysis, 2005)
This article studies the existence of solutions to boundary-value problems for second order multi-valued perturbed differential inclusions under the mixed Lipschitz and Carathéodory conditions. The existence of extremal solutions is also obtained under certain monotonicity conditions and the weaker nonconvexity conditions for multi-valued functions.